Tomorrow, when the war began - Marsden, John, 1950- (Boston : Houghton Mifflin, 1995)
Seven Australian teenagers return from a camping trip in the bush to discover that their country has been invaded and they must hide to stay alive.
"First published 1993 ... Australia"--T.p. verso.
Notable/Best Books (A.L.A.).
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Survival -- Fiction; War -- Fiction; Survival skills -- Fiction; War stories; Australia -- Fiction; Australia -- Fiction